2022
DOI: 10.1038/s41598-022-22359-x
|View full text |Cite
|
Sign up to set email alerts
|

Mandarin Biochar-TETA (MBT) prepared from Citrus reticulata peels for adsorption of Acid Yellow 11 dye from water

Abstract: Dehydration technique with 80% sulfuric acid was used to create a novel biochar from mandarin peel wastes followed by condensate with triethylenetetramine (TETA) to give Mandarin Biochar-TETA (MBT). BJH, BET, FTIR, SEM, DSC, TGA, and EDX studies were used to characterise the MBT. The capacity of the newly developed biochar to remove Acid Yellow 11 (AY11) dye from a water solution was studied. The pH of AY11 dye adsorption was found to be best at pH 1.5. Using 100 ppm AY11 dye as a beginning concentration and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 84 publications
1
32
0
Order By: Relevance
“…On the other hand, the removal percentage remains low when removing AY11 dye from PPAC adsorbent with a high initial concentration because of the empty active sites are unable to adsorb fresh dyes once they have been occupied by a certain amount of AY11 dye. Eleryan et al 6 and El Nemr et al 70 showed similar results in the Acid Yellow 11 dye removal studies.…”
Section: Ay11 Dye Adsorption On Ppacmentioning
confidence: 65%
See 1 more Smart Citation
“…On the other hand, the removal percentage remains low when removing AY11 dye from PPAC adsorbent with a high initial concentration because of the empty active sites are unable to adsorb fresh dyes once they have been occupied by a certain amount of AY11 dye. Eleryan et al 6 and El Nemr et al 70 showed similar results in the Acid Yellow 11 dye removal studies.…”
Section: Ay11 Dye Adsorption On Ppacmentioning
confidence: 65%
“…There are numerous methods of dye-house effluent treatment like coagulation/flocculation 25 , oxidation with chemical 26 , biological treatment 27 , advanced oxidations [28][29][30][31] , electrochemical treatment 32 , photo-degradation [33][34][35][36] and adsorption treatment 6,8,20,37,38 . One of these methods with the highest preference is the adsorption method for dye removal using activated carbon 39 .…”
mentioning
confidence: 99%
“…It is clear from Table 2 that the (1/ n ) values were less than 1, demonstrating that the surface nature of the MG-OPAC is heterogeneous and beneficial for the absorption process. The ' n ' value is > 1, indicating that the physical mechanism of Cr 6+ ions adsorption onto MG-OPAC is favourable 74 , 75 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, rocks can strongly absorb various pollutants from contamination 27,28 . In order to keep dyeing in industrial applications, more affordable materials for color (dye) removal must be found 11,29 . Acid Yellow 17 (AY17) dye is one of the most widely applied dyes in the paper, food, and textile industries 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Brazil, China, Turkey, Egypt, Spain, Japan, Italy and South Korea are the nations with the highest output rates. Mandarin peels, which make up between 8% and 14% of the weight of the fruit used to make fruit juice, are released into the environment 29 . Most uses of mandarin peels are in the fertilizer, fuel and animal feed industries, as well as in the powder and paint business 4,30 .…”
Section: Introductionmentioning
confidence: 99%